2021
DOI: 10.3390/en14237983
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Calculations of Pinus brutia Derivatives and Its Response to Light in a Au/n-Si Device

Abstract: In this study, the performance of an organic dye obtained from the bark of the red pine (Pinus brutia) tree growing in Muğla/Turkey as an interface layer in the Au/n-Si Schottky diode (SD) structure was evaluated. For this purpose, at first, the optimized molecular structure, the highest occupied molecular orbital (HOMO), and the lowest unoccupied molecular orbital (LUMO) simulations of the organic dye were calculated by the Gauss program and it was theoretically proven that the dye exhibits semiconducting pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…According to the TE method, the ideality factor and barrier height are determined in a linear region of the forward bias I-V characteristics. A detailed explanation of the calculation of these parameters using the TE method can be found in the literature [31,32]. Furthermore, the junction resistance (R j ) of the diodes is calculated with the dV/dI formula from the I-V data.…”
Section: Resultsmentioning
confidence: 99%
“…According to the TE method, the ideality factor and barrier height are determined in a linear region of the forward bias I-V characteristics. A detailed explanation of the calculation of these parameters using the TE method can be found in the literature [31,32]. Furthermore, the junction resistance (R j ) of the diodes is calculated with the dV/dI formula from the I-V data.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in RR with increasing intensity can be explained by the increase in the reverse bias current while the forward bias current remains almost unchanged. Furthermore, the variation of η with intensity indicates that current mechanisms other than ideal thermionic emission, such as tunneling and recombination, may also be active in the device [60].…”
Section: Resultsmentioning
confidence: 99%
“…Ulusan et al [40] found that the N SS values varied from 5.6×10 13 eV −1 cm −2 to 2.0×10 12 eV −1 cm −2 for Au/Si 3 N 4 /p-GaAs junction. Yilmaz et al [41] reported that Nss values decreased from 4.268 × 10 15 eV −1 cm −2 to 1.587 × 10 15 eV −1 cm −2 in the dark condition for Au/Pinus brutia/n-Si MIS diode. The N ss values of interfacial state concentration of the Ag/MG/p-InP MIS contact is coherent with those of above indicated works.…”
Section: Interfacial Analysis Of the Ag/mg/p-inp Contactmentioning
confidence: 99%
“…The N ss values of interfacial state concentration of the Ag/MG/p-InP MIS contact is coherent with those of above indicated works. The MG film layer results in a significant alteration of interface state that the MIS interface is sharp and passive [41][42][43]. The MG interlayer raises the BH by the alteration of the crystal substrate surfaces and the chemical interactions at the MIS interfacial region.…”
Section: Interfacial Analysis Of the Ag/mg/p-inp Contactmentioning
confidence: 99%